Dendrite‐Free Nanocrystalline Zinc Electrodeposition from an Ionic Liquid Containing Nickel Triflate for Rechargeable Zn‐Based Batteries. Issue 8 (28th January 2016) - Liu, Zhen; Cui, Tong; Pulletikurthi, Giridhar; Lahiri, Abhishek; Carstens, Timo; Olschewski, Mark; Endres, Frank
Abstract: Metallic zinc is a promising anode material for rechargeable Zn‐based batteries. However, the dendritic growth of zinc has prevented practical applications. Herein it is demonstrated that dendrite‐free zinc deposits with a nanocrystalline structure can be obtained by using nickel triflate as an additive in a zinc triflate containing ionic liquid. The formation of a thin layer of Zn–Ni alloy (η‐ and γ‐phases) on the surface and in the initial stages of deposition along with the formation of an interfacial layer on the electrode strongly affect the nucleation and growth of zinc. A well‐defined and uniform nanocrystalline zinc deposit with particle sizes of about 25 nm was obtained in the presence of Ni II . Further, it is shown that the nanocrystalline Zn exhibits a high cycling stability even after 50 deposition/stripping cycles. This strategy of introducing an inorganic metal salt in ionic liquid electrolytes can be considered as an efficient way to obtain dendrite‐free zinc. Abstract : Deposits and returns : A dendrite‐free zinc deposit with a nanocrystalline structure is obtained when nickel triflate is used as an additive in a zinc triflate containing ionic liquid (IL). The formation of a thin layer of Zn–Ni alloy and a solid electrolyte interface (SEI) layer on the electrode affect the nucleation and growth of zinc.